Ships for the Seven Seas Philadelphia Shipbuilding in the Age of Industrial Capitalism - Heinrich, Thomas (Johns Hopkins University Press, 2020)
Thomas R. Heinrich explores American shipbuilding from the workshop level to subcontracting networks spanning the Delaware Valley.Winner of the North American Society for Oceanic History's John Lyman Book AwardOriginally published in 1996. Sustained by a skilled work force and the Pennsylvania iron and steel industry, Philadelphia shipbuilders negotiated the transition from wooden to iron hull construction earlier and far more easily that most other builders. Between the Civil War and World War I, Philadelphia emerged as the vital center of American shipbuilding, constructing a wide variety of vessel types such as passenger liners, freighters, battleships, and cruisers.In Ships for the Seven Seas, Thomas R. Heinrich explores this complex industry from the workshop level to subcontracting networks spanning the Delaware Valley. He describes entrepreneurial strategies and industrial change that facilitated the rise of major shipbuilding firms; how naval architecture, marine engineering, and craft skills evolved as iron and steel overtook wood as the basic construction material; and how changes in domestic and international trade and the rise of the American steel navy helped generate vessel contracts for local builders. Heinrich also examines the formation of the military-industrial complex in the context of naval contracting.Contributing to current debates in business history, Ships for the Seven Seas explains how proprietary ownership and batch production strategies enabled late nineteenth-century builders to supply volatile markets with custom-built steamships. But large-scale naval construction in the 1920s eroded production flexibility, Heinrich argues, and since then, ill-conceived merchant marine policies and naval contracting procedures have brought about a structural crisis in American shipbuilding and the demise of the venerable Philadelphia shipyards.